Biochemistry - Campbell, Mary K.; Farrell, Shawn O.; Campbell, Mary K. (Australia, Thomson, 2003)
Noted for their ability to demonstrate the connection between biochemistry and students' lives, the authors draw students into the material with stellar coverage of the latest research. The standard setting illustration program enhances students understanding.
Includes bibliographical references; Glossary G1-G13p; Index I1-I20p
Keywords: Biochemistry; Chemistry